Trans-axillary single port insufflation technique-assisted endoscopic surgery for breast diseases: Clinic experience, cosmetic outcome and oncologic result - Wang, Xuefei; Wan, Xin; Li, Lifang; Liu, Xu; Meng, Ran; Sun, Xiaohu; Xiao, Chunhua (Frontiers in Oncology, 2023)
Purpose: With an increasing demand for postoperative cosmetic effects in breast diseases, the single port by trans-axillary incision and air-inflation system, which provided better space and spared the assistant the effort of retraction, is widely used in clinic surgical treatment for multiple breast diseases. Methods：According to inclusion and exclusion criteria, patients who underwent trans-axillary single-incision surgery at Tianjin Medical University Cancer Hospital between December 2020 and July 2022 were included in the study. We collected and analyzed data on age, fertility history, ultrasound grade, clinical stage, pathological results, oncological prognosis, patient-centered cosmetic outcome, etc. Result: A total of 115 cases were included, of which 33 patients with benign disease underwent mass resection, 68 patients with malignant tumors underwent mastectomy. 10 patients had a special type of breast lesion. A mastectomy was performed in 4 patients with male mammary gland development. Of the 115 cases, the maximum mass diameter was 3.00 ± 1.644 (0.6–8.5) cm. Blood loss during surgery was 85.77 ± 50.342 (10-200) ml. The surgery took 131.84 ± 59.332 (30-280) minutes to complete. The patient spent a total of 5.05 ± 2.305 (2-18) days in the hospital. And the length of surgical incision in all patients was 3.83 ± 0.884 (3-8) cm. All patients were very satisfied with the appearance of their breasts after dressing. 94.78% of patients were satisfied with the position of the incision. Conclusions: Through this study, we believe that in benign breast diseases and malignant breast tumors, trans-axillary single port insufflation technique-assisted endoscopic surgery has oncological safety and an aesthetic effect for most people with breast diseases.